Hartree-fock cluster investigations of electronic structure and nuclear quadrupole interaction in the superionic conductor li3n - Mishra, Kailash C.; Das, Tara Prasad; Kelires, Pantelis C. (My University, 1987)
The nuclear quadrupole interactions for7Li and14N nuclei are studied for lithium nitride crystal using the Hartree-Fock cluster procedure to obtain the electronic structure. The influence of the Madelung potential due to the ions outside the cluster was incorporated in a first-principle manner. Our results for the quadrupole coupling constants will be compared with experimental data and the results of a recent band calculation.
Keywords: Electronic structure; Ions; Lithium; Nitrides